2018
DOI: 10.2136/sssaj2018.02.0082
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soil Organic Carbon, pH, Electrical Conductivity, and Water Stable Aggregates to Long‐Term Annual Manure and Inorganic Fertilizer

Abstract: Core Ideas Long‐term annual application of manure maintained the soil pH but inorganic fertilizer decreased it. Manure application increased soil organic carbon (SOC) and total nitrogen (TN). Higher manure rate helps in improving the water stable aggregates compared to inorganic fertilizer at 0‐ to 10‐cm depth. Manure enhances soil fertility and crop yield; however, an optimum rate of manure application is important to avoid any negative impacts to soils and the environment. This study was conducted to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
77
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 30 publications
15
77
2
Order By: Relevance
“…It is noticed from this current study that fertilizer treatment 30F recorded the highest pH values whereas NPK recorded the lowest at both depths compared to other treatments. This finding agrees with that of Ozlu and Kumar (2018) who observed that higher manurecontaining fertilizers increased pH values compared to higher doses of chemical fertilizer sources. The decline in pH values noticed in the NPK treatment in our current study could be connected with nitrification and acidification activities (Liang et al 2012).…”
Section: Soil Ph Total Organic Carbon and Total Nitrogensupporting
confidence: 92%
See 3 more Smart Citations
“…It is noticed from this current study that fertilizer treatment 30F recorded the highest pH values whereas NPK recorded the lowest at both depths compared to other treatments. This finding agrees with that of Ozlu and Kumar (2018) who observed that higher manurecontaining fertilizers increased pH values compared to higher doses of chemical fertilizer sources. The decline in pH values noticed in the NPK treatment in our current study could be connected with nitrification and acidification activities (Liang et al 2012).…”
Section: Soil Ph Total Organic Carbon and Total Nitrogensupporting
confidence: 92%
“…It is clearly observed from this study that the long-term fertilizer treatments markedly impacted on pH values in the surface layer only. Ozlu and Kumar (2018) and Liang et al (2012) also noticed similar trends, where fertilizer treatments considerably influenced the pH values in the 0-10 and 10-20 cm compared to the 20-30 and 30-40 cm layers. It is noticed from this current study that fertilizer treatment 30F recorded the highest pH values whereas NPK recorded the lowest at both depths compared to other treatments.…”
Section: Soil Ph Total Organic Carbon and Total Nitrogensupporting
confidence: 55%
See 2 more Smart Citations
“…Organic fertilizers (manure, humus, etc.) are known to contain nutrients [35] in a safe form for plants and the environment. Accordingly, that is why they are recommended for use by Council Regulation (EC) No.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%